2001
DOI: 10.1161/01.cir.103.8.1051
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Calcification on the Biomechanical Stability of Atherosclerotic Plaques

Abstract: Background-Increased biomechanical stresses in the fibrous cap of atherosclerotic plaques contribute to plaque rupture and, consequently, to thrombosis and myocardial infarction. Thin fibrous caps and large lipid pools are important determinants of increased plaque stresses. Although coronary calcification is associated with worse cardiovascular prognosis, the relationship between atheroma calcification and stresses is incompletely described. Methods and Results-To test the hypothesis that calcification impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
305
3
10

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 531 publications
(333 citation statements)
references
References 24 publications
15
305
3
10
Order By: Relevance
“…When patients were divided by OSA severity into normal (AHI <10), mild (AHI [10][11][12][13][14][15][16][17][18][19][20], and severe (AHI >20) groups, the odds for any vessel involvement were 9.6 (95% CI: 1.1-85.3) for mild OSA and 42.1 (95% CI: 4.1-428.4) for moderate to severe OSA. These odds were adjusted for age, sex, race, hypercholesterolemia, and smoking history.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When patients were divided by OSA severity into normal (AHI <10), mild (AHI [10][11][12][13][14][15][16][17][18][19][20], and severe (AHI >20) groups, the odds for any vessel involvement were 9.6 (95% CI: 1.1-85.3) for mild OSA and 42.1 (95% CI: 4.1-428.4) for moderate to severe OSA. These odds were adjusted for age, sex, race, hypercholesterolemia, and smoking history.…”
Section: Resultsmentioning
confidence: 99%
“…Overnight polysomnography was performed at nationally accredited sleep centers, and final diagnosis with apnea-hypopnea index (AHI; measure of the severity of disease) was available in all patients included in this study. Obstructive sleep apnea was further classified as no OSA (AHI <10), mild OSA (AHI [10][11][12][13][14][15][16][17][18][19][20], and severe OSA (AHI> 20). The number of vessels involved was defined as 0 if there was no stenosis and 1 if any stenosis or plaque was present.…”
Section: Imaging Techniquementioning
confidence: 99%
“…Intimal, or more precisely neointimal, calcification is associated with atherosclerosis (5) and occurs in the absence of renal failure. Whether it has any clinical significance beyond serving as a marker of advanced atherosclerosis is unclear because calcification may actually stabilize plaques (6,7). Calcification in the medial layer is independent of atherosclerosis or inflammation, occurs in small arteries in addition to large arteries, and is thought to be detrimental by decreasing arterial compliance (8).…”
Section: Introductionmentioning
confidence: 99%
“…Huang et al reported that increases in percent area of plaque occupied by calcium in coronary plaques was associated with decreased stress in the plaque, whereas increased plaque lipid content was correlated with increased stress. 40 On the other hand, some investigators argue that certain types of calcifications may increase risk. 32,33 For example, a shearing plane can be created between calcified and noncalcified plaque, predisposing to rupture in response to a stress such as angioplasty.…”
Section: Discussionmentioning
confidence: 99%